A methodological approach to analysing customer sentiment and language use for assessing service quality in AirAsia's online reviews - Idris, Sheema Liza; Zainuddin, Anizah (Universiti Teknologi Mara Selangor, 2024)
This paper focuses on the research methods used to analyse customer sentiment and language patterns in online reviews to evaluate service quality. The study uses TripAdvisor reviews of AirAsia from the prepandemic period (2017-2019). It applies the SERVQUAL model to assess five key dimensions of service quality: tangibility, reliability, responsiveness, assurance, and empathy. Qualitative and quantitative methods were used, including sentiment analysis and thematic coding, to interpret customer feedback accurately. The process involved collecting relevant reviews, preparing the data, analysing customer sentiment, and mapping the findings to the SERVQUAL dimensions. Tools such as NVivo and Python libraries were employed for data processing and analysis. The paper highlights the challenges faced during the study, such as handling biased sentiments and language variations, and outlines steps to ensure reliability and validity. This research methodology offers a systematic way to understand customer experiences and provides a valuable approach for businesses looking to improve service quality based on customer feedback.